Hibiscus sabdariffa L.: ESTABILIDADE DA ATIVIDADE ANTIOXIDANTE E CONSTITUINTES QUÍMICOS APÓS PREPARO DO CHÁ - Andressa Ândria Martins RIBEIRO; Diegue Henrique Nascimento MARTINS; Gabriela Roso CIBIN; Dâmaris SILVEIRA; Pérola de Oliveira MAGALHÃES; Yris Maria FONSECA-BAZZO (Federal Council of Pharmacy, 2018)
Hibiscus sabdariffa L. is used due to its peculiar taste and its healing properties. The literature reports antioxidant, anti-inflammatory and antidiabetic properties for this plant. Hibiscus is used as a tea, obtained from the infusion of parts of the plant, precisely its dried calyx. Due to its properties, the consumption of this tea in Brazil has been growing. Quality evaluation is important to guarantee the efficacy and safety of such products. In this study, three brands of H. sabdariffa L. tea were evaluated for their antioxidant properties, as well as their phytochemical profile by HPLC/ DAD. The methods of lipid peroxidation and inhibition of the formation of the phosphomolybdenum complex were used to evaluate the antioxidant activity. To better guide the safe consumption of this tea, the stability of the antioxidant activity was assessed 1 and 12 hours after preparation. In the chromatographic analysis, the presence of neochlorogenic acid was detected in all evaluated brands. The tea showed antioxidant activity in the two used methods. However, antioxidant activity tended to be lower after 12 hours of tea preparation. Therefore, to preserve the activity, the H. sabdariffa L. tea should be used up to 12 hours after preparation.